THE INFLUENCE OF THE USE OF GADGETS AS A LEARNING RESOURCE AND INTEREST IN LEARNING ON THE LEARNING OUTCOMES OF GRADE X STUDENTS IN ECONOMICS SUBJECTS AT MUHAMMADIYAH 11 HIGH SCHOOL IN EAST JAKARTA - Ramadhina, Yuqa Putri; Nurjanah, Siti; Pratama, Aditya (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2023)
This study aims to determine the effect of using gadgets as learning resources and interest in learning on the learning outcomes of grade X students in economics subjects at SMA Muhammadiyah 11 East Jakarta. This study uses a quantitative approach and survey method. The number of samples in this study was 104 students. The data used were primary and secondary data. Primary data was obtained using a closed questionnaire while secondary data was obtained from the Summative Assessment End of Even Semester. The data analysis used in this research is Path Analysis with the help of SPSS version 25. The results of the first hypothesis research show that the use of gadgets as a learning resource has a direct positive effect on student learning outcomes with a magnitude of 0.439. In the second hypothesis, learning interest has a direct positive effect on student learning outcomes with a magnitude of 0.549. Furthermore, the third hypothesis is accepted, which means that the use of gadgets as a learning resource has a direct positive effect on learning interest with a magnitude of 0.846. And the fourth hypothesis is accepted, meaning that there is an indirect effect of using gadgets as learning resources on student learning outcomes through learning interest of 0.464 with a p value <0.05, which means that learning interest has a role in mediating the use of gadgets as learning resources on student learning outcomes. Hence, the desire to learn has a dual impact on students' educational achievements.